Heart Rate Changes in Response to Mechanical Pressure Stimulation of Skeletal Muscles Are Mediated by Cardiac Sympathetic Nerve Activity - Watanabe, Nobuhiro; Hotta, Harumi (Frontiers in Neuroscience, 2017)
Stimulation of mechanoreceptors in skeletal muscles such as contraction and stretch elicits reflexive autonomic nervous system changes which impact cardiovascular control. There are pressure-sensitive mechanoreceptors in skeletal muscles. Mechanical pressure stimulation of skeletal muscles can induce reflex changes in heart rate (HR) and blood pressure, although the neural mechanisms underlying this effect are unclear. We examined the contribution of cardiac autonomic nerves to HR responses induced by mechanical pressure stimulation (30 s, 10 N/cm2) of calf muscles in isoflurane-anesthetized rats. Animals were artificially ventilated and kept warm using a heating pad and lamp, and respiration and core body temperature were maintained within physiological ranges. Mechanical stimulation was applied using a stimulation probe 6 mm in diameter with a flat surface. Cardiac sympathetic and vagus nerves were blocked to test the contribution of the autonomic nerves. For sympathetic nerve block, bilateral stellate ganglia and cervical sympathetic nerves were surgically sectioned, and for vagus nerve block, the nerve was bilaterally severed. In addition, mass discharges of cardiac sympathetic efferent nerve were electrophysiologically recorded. Mechanical stimulation increased or decreased HR in autonomic nerve-intact rats (range: −56 to +10 bpm), and the responses were negatively correlated with pre-stimulus HR (r = −0.65, p = 0.001). Stimulation-induced HR responses were markedly attenuated by blocking the cardiac sympathetic nerve (range: −9 to +3 bpm, p < 0.0001) but not the vagus nerve (range: −75 to +30 bpm, p = 0.17). In the experiments with cardiac sympathetic efferent nerve activity recordings, mechanical stimulation increased or decreased the frequency of sympathetic nerve activity in parallel with HR (r = 0.77, p = 0.0004). Furthermore, the changes in sympathetic nerve activity were negatively correlated with its tonic level (r = −0.62, p = 0.0066). These results suggest that cardiac sympathetic nerve activity regulates HR responses to muscle mechanical pressure stimulation and the direction of HR responses depends on the tonic level of the nerve activity, i.e., bradycardia occurs when the tonic activity is high and tachycardia occurs when the activity is low.